Sinergitas Penguatan Dakwah Dan Kemandirian Perekonomian Melalui Perencanaan Gedung Serbaguna Sebagai Pengembangan Amal Usaha PCM Sawit Boyolali - Guntur Nugroho; As'at Pujianto; Chusnul Azhar; Fathurrahman Kamal; Ghoffar Ismail; Gita Danu Pranata; Arini Hidayah; Ulfah Dian Indrayani (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
Community service programs have been implemented at the head of the Muhammadiyah Sawit Boyolali branch. The purpose of the community service program is to plan the development of da'wah through the development of Muhammadiyah business charity within the PCM Sawit Boyolali company. From the results of discussions held by the service team and management of the PCM Branch Leadership, it was agreed that the development of Muhammadiyah business charity was realized by planning the PCM Multipurpose Building. The problem that arises is that the land that will be used as the location for the construction of the Multipurpose Building is not yet available. The effort made is to invite all company residents to participate in the construction building. From the joint efforts of the Muhammadiyah Sawit branch leader, Boyolali received waqf land from company residents in the PCM Sawit environment. With the waqf land from the company's residents, the problems faced related to the location of the building placement have been solved.